2021
DOI: 10.1126/sciadv.aay5496
|View full text |Cite
|
Sign up to set email alerts
|

De-scattering with Excitation Patterning enables rapid wide-field imaging through scattering media

Abstract: Nonlinear optical microscopy has enabled in vivo deep tissue imaging on the millimeter scale. A key unmet challenge is its limited throughput especially compared to rapid wide-field modalities that are used ubiquitously in thin specimens. Wide-field imaging methods in tissue specimens have found successes in optically cleared tissues and at shallower depths, but the scattering of emission photons in thick turbid samples severely degrades image quality at the camera. To address this challenge, we introduce a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In this section we present numerical results on synthetic test datasets to validate our trained inverse model. All experiments used only 32 patterned illuminations which is nearly an order of magnitude less than the current state of the art 8 .…”
Section: Numerical Results On Synthetic Test Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we present numerical results on synthetic test datasets to validate our trained inverse model. All experiments used only 32 patterned illuminations which is nearly an order of magnitude less than the current state of the art 8 .…”
Section: Numerical Results On Synthetic Test Datamentioning
confidence: 99%
“…They used coded excitations and single-pixel detection. We proposed 'De-scattering by Excitation Patterning (DEEP)' 8 . Instead of single-pixel detection, we used wide-field detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective illumination can be implemented with either one-photon microscopy 4 8 or multiphoton microscopy. 9 17 Multiphoton microscopy is more robust to tissue scattering than one-photon microscopy because the excitation light of multiphoton microscopy has a longer wavelength. Therefore, selective illumination generated by multiphoton microscopy has higher precision and less cross-talk when imaging at a few hundred microns deep in the mouse brain.…”
Section: Light Sculpture For Parallel Excitationmentioning
confidence: 99%
“…For the latter, we proposed the techniques of focal modulation [ 22 ] and extended detection followed by computation reconstructions [ 18 ] for LSTFM. Zheng et al also demonstrated a de-scattering method by taking advantage of patterned nonlinear excitation and computational-assisted wide-field detection [ 23 ]. All these methods are effective in enhancing axial resolution and background rejection.…”
Section: Introductionmentioning
confidence: 99%